Evaluación del proceso de obtención de ajo negro a partir de distintas variedades de Allium Sativum (AJO). - Calderón Pérez, Rafael Antonio (2015)
In the present study the process of getting black garlic is evaluated from different varieties of garlic, establishing varieties with higher nutritional properties between garlic female, male and Peru, determining the appropriate times (30 days and 40 days) by applying different temperatures (60 ° C - 70 ° C) for the highest concentration of selenium in the black garlic. The sample size per treatment was 1kg, recital 12 treatments were used 12 kg. 2 replicates 24 kg of garlic, this represents 8 Kg Peruvian garlic, 8 kg male garlic and 8 kg Garlic female and adaptation process consisted of placing each kilo of garlic in wooden boxes, we introduce the boxes the three varieties of garlic in stoves at 60 ° C and 70 ° C for a time of 30 and 40 days respectively, performing color verification garlic every 10 days. To determine the concentration of selenium proceeded to use, atomic absorption spectroscopy to measure the specific concentrations of material in a mixture, study Laboratory Multianalítyca with the reference method AOAC 996.17 addition proceeded to evaluate fat, protein, ash and fiber in food science laboratory of State Technical University Quevedo. The results of selenium with respect to Factor A (garlic varieties) (52.16%), Factor B (Temperature) (52.16%), Factor C (Time) (45.02%). In conclusion Selenium best results in regard to Factor A (garlic varieties) Peruvian (52.16%) garlic, Factor B (Temperature) 70 ° C (52.16%), Factor C (Time) 40 days (45.02%). It is recommended in Factor A: The use of the variety (Peruvian Ajo) plus this has content: Ash (3.91%), fiber (10.19%), fat (0.08%), protein (16, 34%) and selenium (52.16%), Factor B: temperature 70 ° C this addition has content: Ash (2.67%), fiber (7.72%), fat (0.23%) , Protein (11.32%), Selenium (52.16%), Factor C: time (40 DAYS) plus this has content: Ash (2.66%), fiber (7.71%), fat (0.23%), protein (11.31%), Selenium (45.02%).